Analisis Peningkatan Sinergi Antara Pasar Tradisional Dan Modernitas Guna Mencapai Penyeluruhan Pembangunan Ekonomi Masyarakat Indonesia - Fitria Futri; Mifta Amalia; Dewi Aminah Lestari; Esavira Yunitasya; Muhamad Angga Munawar; Maya Panorama (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
The purpose of this article is to: 1) Map the allocation chart of traditional and modern markets 2) Review the classification of traditional and modern markets. 3) Evaluate the range of traditional and contemporary market services; 4) Analyze the advantages of traditional and contemporary market players; 5) Formulate policy proposals to strengthen the synergy between traditional markets and modern markets. Strengthening an effective and efficient intra-regional trading system requires support from all stakeholders, including the government, private business actors, BUMN and science. Therefore, the implementation of all predetermined action plans requires strong support, commitment and collaboration from all stakeholders.